Pengaruh Hasil Belajar Mata Pelajaran Produktif terhadap Kesiapan Kerja Siswa Sekolah Menengah Kejuruan - Tesya Regina Putri; Hambali Hambali (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2022)
This study aims to see the level of work readiness that is influenced by the learning outcomes of productive subjects of class XI students of the Electrical Power Installation Engineering Department (TITL) at SMK Negeri 2 Sijunjung. This type of research uses a causal relationship method with quantitative data. The population in this study were class XI students of the Electrical Power Installation Engineering Department at SMK Negeri 2 Sijunjung. The sampling technique used is saturated sampling with a total sample of 70 students. For data collection techniques using documentation and questionnaire techniques measured by a Likert scale. The analysis used are: simple linear regression analysis and t test. The results of the study indicate that learning outcomes have a significant effect on work readiness, this is evidenced by the value of rcount being greater than rtable. From the t-test also obtained the results of the calculation of tcount greater than ttable which means that Ha is accepted and H0 is rejected, so it can be concluded that there is a significant influence between learning outcomes on the work readiness of class XI TITL students at SMK Negeri 2 Sijunjung.